Association of sociodemographic and environmental factors with allergic rhinitis and asthma - Báló Barnabás (Acta climatologica, 2012)
Asthma and allergic rhinitis can play an important role in the quality of life, and its components are not clearly understood. The aim of the study is to analyse the role of socio-demographic and environmental factors in developing allergic asthma and rhinitis. The data set of the study is a questionnaire-based survey, with altogether 3666 interviewees. Altogether 26 socio-demographic and environmental variables are considered in the statistical analysis. Furthermore, seven resultant variables inducing allergic reactions were considered. They are as follows: dust, pollen, food, skin, pet, medicine and insect byte. For this, canonical correlation analysis (CCA) and a factor analysis with special transformation was performed in order to find out the strength and direction of the socio-demographic and environmental factors examined in forming certain allergic diseases.